Transformations in Socio-Economic Development of the Gulf Group States - Shkvarya, Lyudmila Vasilievna; Frolova, Elena Dmitrievna (Economy of Regions, 2017)
The article is devoted to the national economy transformations of the GCC States (Cooperation Council for the Arab States of the Gulf countries). This paper analyzes the dynamics of socio-economic development of the Gulf Group countries for the last 10 years, compares and systematizes the traditional and unique statistical data in order to prove the hypothesis that the positive dynamics was not only due to the high hydrocarbon prices on the global market but also to the successful structural transformation. The growth of the regional economy in the conditions of an almost threefold drop in world oil prices over the past three years is shown. We use systemic approach, comparative and statistical analysis. As the analysis of economic situation and development in the GCC countries at the current stage shows, all of them need to change the structure of the national economy and diversify it in order to reduce the dependence from mining industries, world prices fluctuations. This paper proposes a number of practical considerations and appropriate measures for the formation of more rational structure of the national economies, including the diversification of the sources of budget revenues through expanding industrialization; accelerating development of solid minerals and the creation of new industries using them. As Gulf States belong to the group of emerging countries and the structure of their national economies is similar with the Russian economy, the factors of the positive changes of the national economies will be useful for Russian and foreign researchers.